Pluralisme hokum dan kinamika hak atas property: Indonesian translation of Legal pluralism and dynamic property rights - Meinzen-Dick, Ruth S.; Pradhan, Rajendra (HuMa, 2006)
Conventional conceptions of property rights focus on static definitions of property rights, usually as defined in statutory law. However, in practice there is co-existence and interaction between multiple legal orders such as state, customary, religious, project and local laws, all of which provide bases for claiming property rights. Legal anthropological approaches that recognize this legal pluralism are helpful in understanding this complexity. Individuals may choose one or another of these legal frameworks as the basis for their claims on a resource, in a process referred to as “forum shopping.” Legal pluralism can create uncertainty especially in times of conflict because any individual is unlikely to have knowledge of all types of law that might be relevant, and because rival claimants can use a large repertoire to lay claim to a resource. However, at the same time the multiple legal frameworks facilitate considerable flexibility for people to maneuver in their use of natural resources. Legal pluralism also introduces a sense of dynamism in property rights, as the different legal frameworks do not exist in isolation, but influence each other, and can change over time. Unless these aspects of property rights are recognized, changes in statutory law intended to increase tenure security may instead increase uncertainty, especially for groups with less education and contacts. This paper illustrates the implications of legal pluralism for our understanding of natural resource management and policies toward resource tenure, using the example of water rights. (text of Abstract)